Control of the Spin Dynamics of Single‐Molecule Magnets by using a Quasi One‐Dimensional Arrangement. (8th May 2018) - Katoh, Keiichi; Yamashita, Satoshi; Yasuda, Nobuhiro; Kitagawa, Yasutaka; Breedlove, Brian K.; Nakazawa, Yasuhiro; Yamashita, Masahiro
Abstract: Magnetic dipole interactions are dominate in quasi one‐dimensional (1D) molecular magnetic materials, in which TbNcPc units (Tb 3+ =terbium(III) ion, Nc 2− =naphthalocyaninato, Pc 2− =phthalocyaninato) adopt a structure similar to TbPc2 single‐molecule magnets (SMMs). The magnetic properties of the [TbNcPc] 0/+ (neutral 1 and cationic 2 ) with 1D structures are significantly different from those of a magnetically diluted sample (3 ). In particular, the magnetic relaxation time ( τ ) of 2 in the low‐temperature region is five orders of magnitude slower than that of 3 . Furthermore, the coercivity ( H C ) of 2 remained up to about 20 K. The single‐ion anisotropy of Tb 3+ ions in a 1D structure and the magnetic dipole interactions acting among molecules determines the direction of the magnetic properties. These results show that the spin dynamics can be improved by manipulating the arrangement of SMMs in the solid state.